A Six Months Analysis of COVID-19 Death : Experience From a Tertiary Hospital, Chattogram - Roy Biswas, Rajat Sanker; Nath, Jishu Deb; Nisha, Fatema Emrose; Sarker, Prasenjit (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background : COVID 19 pandemic had taken away lots of human life prematurely worldwide and death laid its icy hands also on Bangladesh. So, objectives of this study were to explore the monthly distributions, age, sex, comorbidities, localities and duration of hospital stay among the COVID 19 death cases. Materials and methods: In this observational study six months hospital death registries were collected and explored for monthly distributions, age, sex, comorbidities, localities and hospital stay. RT-PCR positive confirmed 113 COVID deaths were enrolled and suspected COVID deaths were excluded. Ethical clearance from the hospital authority was taken before hand. Data was compiled and analyzed by SPSS-20. Results: There was a low frequency of death in the months May-2021 and October-2021(7.1% and 2.7% respectively) but more during June -2021 to September 2021 (12.4%, 16.8%, 42.5% and 18.6% respectively). Female deaths were more than male deaths (53.1% vs 46.9%, p<0.05). Age more than 51 years were the most vulnerable where 26(23%) deaths were at age group 51- 60 years, 39(34.5%) deaths were at 61-70 years and 22(19.4%) deaths were more than 71 years. Mean age of death was found 60.66 years and mean duration of hospital stay was found 9.45 days. Maximum duration of hospital stay was 45 days for one patient. Co-morbidities of death cases revealed 52(46.00%) patients had DM and HTN both, 17(15.0%) patients had HTN, 16(14.1%) had DM, 3(2.6%) had BA and COPD, 4(3.5%) had CKD, 2(1.7%) had cancer, 3(2.6%) had CVD, 19(16.8%) had IHD and 16(14.1%) patients had no co-morbidities. Locality of the death cases revealed 44(38.9%) patients came from rural areas and 69(61.1%) came from urban areas. Conclusion: Higher age group and multiple comorbidities specially DM, HTN and IHD were related with COVID deaths mostly found in our study. JCMCTA 2022 ; 33 (1) : 46-49